Leadership Management Training to Improve the Competence of School Principals: Pelatihan Manajemen Kepemimpinan Untuk Meningkatkan Kompetensi Kepala Sekolah - Daga, Agustinus Tanggu; Khristoforus Palli Ngongo; Wilhelmus Yape Kii; Kanisius Kami; Yulita Adelfin Lede; Geterudis Kerans; Etheldreda Rosari Garung; Yohanis Umbu Kaleka; Konradus Doni Kleden (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Improving the competence of school principals is very important and needed in education management. This is because school principals have an important role in determining educational development policies. The aim of this training is to improve the leadership competence of school principals to manage quality education within the scope of the Nusa Cendana Education Foundation (Yapnusda). Leadership management was chosen as the training theme because it suits the problems and needs of schools in Yapnusda. Participants are school principals and school treasurers. The training method is case study. Implementation of training activities starts from preparation, planning, implementation, and evaluation. Based on the survey results, it was concluded that the participants were satisfied with the training activities, the training materials were relevant to the needs and problems at school, and this training activity was useful for their duties as school principals. Training activities improve the training participants' knowledge and understanding of leadership management.